Static Strength Analysis of Upper Structure of Kereta Kapsul Using Finite Element Method with Shell Elements - Aliabudi Yahya (NIM : 13113141), Johan
Preliminary analysis needs to be done on the initial design of the Kereta Kapsul. Finite Element Method is used in performing the analysis because of its accuracy and simplicity. Shell elements are used to model components made of plates to reduce computation loads. This undergraduate thesis aims to analyze the stress of the upper structure of Kereta Kapsul based on Regulation of the Minister of Transport No. 175 of 2015 and the American Society of Civil Engineers 21.2 2008 standard and modify the geometry to obtain the optimum design. The analysis began with geometry and material modeling and is followed by the application of boundary conditions in accordance with the standards. The meshing process is carried out with a first-order quadrilateral element type with size of 10 mm in Base Frame and 15 mm in Body Frame. The next step is the convergence and validation test. Convergent and valid models will be analyzed and modified in case of structural failure. Base Frame failure occurs in case of compression loading according to PM 175 2015 and in the worst case of ASCE 21.2 2008. A modification process of the geometry of Base Frame has been done involving five iterations which resulted in the last model with a mass of 1103 kg with a minimum safety factor of 2.7 in the worst case loading and 2.3 on compression loading.